Experience Sexually Active Adolescents in the Use of Condoms to Prevent HIV/AIDS: Scoping Review - Siti Lisdia Nur Ranni; Sulistyaningsih Sulistyaningsih; Dhesi Ari Astuti (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Sexually active adolescents are vulnerable to HIV/AIDS transmission due to various psychological, socioeconomic, and sociocultural factors. Although condoms are recognized as an effective method for preventing HIV transmission, their use among adolescents remains inconsistent and is influenced by individual experiences and social contexts. This scoping review aimed to map and synthesize evidence on adolescents’ experiences of condom use for HIV/AIDS prevention. Method: This scoping review followed the PRISMA-ScR guidelines and was guided by the Population–Exposure–Outcome–Study Design (PEOS) framework. Literature searches were conducted in PubMed, ScienceDirect, and DOAJ. Eligible studies were full-text articles published between 2021 and 2025 that explored condom use experiences among sexually active adolescents. Data were extracted and critically appraised using Joanna Briggs Institute (JBI) tools. Result: A total of 1,448 records were identified, and eight studies met the inclusion criteria. Five major themes emerged: subjective experiences of condom use, psychosocial factors, socio-cultural norms, trauma and vulnerability, and health systems and services. Key factors influencing condom use included social stigma, limited negotiation skills, restrictive cultural norms, trauma-related experiences, and inadequate access to adolescent-friendly health services. Conclusion: Adolescents’ experiences of condom use are complex and shaped by psychosocial, sociocultural, and structural factors. Effective HIV/AIDS prevention strategies should incorporate culturally sensitive policies, evidence-based interventions, and strengthened adolescent-friendly health services to support safer sexual behaviors among adolescents.